1979
DOI: 10.1126/science.760212
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram Correlates of Higher Cortical Functions

Abstract: By means of two-stage, nonlinear multivariate pattern recognition, electroencephalograms (EEG's) were analyzed during performance of verbal and spatial tasks. Complex scalp distributions of theta-, beta-, and, to a lesser extent, alpha-band spectral intensities discriminated between the two members of a pair of tasks, such as writing sentences and Koh's block design. Small EEG asymmetries were probably attributable to limb movements and other uncontrolled noncognitive aspects of tasks. Significant EEG differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
1

Year Published

1980
1980
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(91 citation statements)
references
References 26 publications
4
85
1
1
Order By: Relevance
“…Decreased alpha in the high-load task is consistent with the notion that the amplitude of this signal is inversely related to the proportion of cortical neurons involved with task performance. Similar patterns of effort-related modulation of the EEG have been found in numerous other investigations (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Although spectral components of healthy adults' EEG have been shown to be sensitive to the mental effort associated with computer-based laboratory tasks, few data exist concerning whether the EEGs of juvenile subjects playing commercial video games will exhibit the similar patterns.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Decreased alpha in the high-load task is consistent with the notion that the amplitude of this signal is inversely related to the proportion of cortical neurons involved with task performance. Similar patterns of effort-related modulation of the EEG have been found in numerous other investigations (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Although spectral components of healthy adults' EEG have been shown to be sensitive to the mental effort associated with computer-based laboratory tasks, few data exist concerning whether the EEGs of juvenile subjects playing commercial video games will exhibit the similar patterns.…”
mentioning
confidence: 74%
“…The peak amplitude at electrode site F, (6-7 Hz) was extracted to represent frontal midline theta in each subject. Average power across a 1-Hz band was used to characterize the alpha rhythm at electrode site 0, (9)(10)(11)(12) Hz) and the mu rhythm at electrode site C, (10)(11)(12)(13). A 3 (Load: resting x watching x playing) by 2 (Group: patient x control) ANOVA on absolute power values yielded no significant effect of group, or Group-by-Load interactions, at any of the measured frequencies.…”
Section: Figmentioning
confidence: 99%
“…According to several authors, [14][15][16][17][18][19][20] dendritic and neuronal losses are always present in epileptic patients. These losses are independent of crisis type, and if we consider the anatomical and histopathological disorders responsible for poor performance by epileptic patients in the auditory skills evaluated in the SSW test, these authors' findings would explain such performance observed in both groups of epileptic patients studied here.…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalography (EEG) correlates of workload have focused upon P300 as a measure of central processing (Israel et * al., 1980) and spatial and temporal dynamic patterns of evoked potentials during mental work (Gevins et al, 1979(Gevins et al, , 1981(Gevins et al, , 1983. These techniques require steady-state workload conditions for averaging.…”
Section: Psychophysiology Of Mental Workloadmentioning
confidence: 99%